The right swipe : a novel - Rai, Alisha (Rai, Alisha. Modern love., 2019)
Rhiannon Hunter may have revolutionized romance in the digital world, but in real life she only swipes right on her career<U+2014>and the occasional hookup. The cynical dating app creator controls her love life with a few key rules: - Nude pics are by invitation only - If someone stands you up, block them with extreme prejudice - Protect your heart. Only there aren't any rules to govern her attraction to her newest match, former pro-football player Samson Lima. The sexy and seemingly sweet hunk woos her one magical night... and disappears. Rhi thought she'd buried her hurt over Samson ghosting her, until he suddenly surfaces months later, still big, still beautiful<U+2014>and in league with a business rival. He says he won't fumble their second chance, but she's wary. A temporary physical partnership is one thing, but a merger of hearts? Surely that<U+2019>s too high a risk<U+2026>